(untitled) (Boston, 2013)
The revised edition of this renowned and bestselling title is the most comprehensive single text on all aspects of biomaterials science. It provides a balanced, insightful approach to both the learning of the science and technology of biomaterials and acts as the key reference for practitioners who are involved in the applications of materials in medicine.
Vật liệu y sinh (Biomedical materials)
Keywords: Vật liệu y sinh,Biomedical materials